Implementasi Penetapan Standar Mutu Melalui Proses Penjaminan Mutu Internal di Universitas Islam Nusantara - Sauri, R. Supyan (Media Nusantara, 2021)
This study aims to describe the implementation of quality standard-setting through the internal quality assurance system (SPMI) process, in improving the quality of input, process, output, and outcome of Higher Education. This is very important considering the performance problems of the study program is so complex, starting from student input, the learning process, meeting quality standards for higher education. This research uses a qualitative approach with a case study method. The technique of collecting data through observation, search documents and archives, and interviews. The results showed the existence of policies and concepts such as documents SPMI academic quality standards and document non-academic quality standards were drawn up by the Directorate of Quality Assurance (DPM) as a reference in formulating the quality standard at the level of the study program, which coordinates with GPM and UPM in the process of determining, implementing, evaluating, controlling, and improving the quality standards of the study program.